The aesthetics of parallelism Rhythm in the Al-Ashbah Sermon - Ali Ghahramani; Solmsz Porshoor (مطالعات زبانی و بلاغی)
The structure of the sentence serves a fundamental function in the beauty of the literary text and inducing its concepts and themes. The sentence should be combined in a way that the audience position is considered. The vocabulary must be put together in a way that their syntagmatic and paradigmatic reach to ear a harmonic and subtle rhythm and their arrangement reflects the purpose and content of the text. The Al-Ashbah Sermon is one of the remarkable sermons of Imam Ali (as) that in addition to deep meanings and contents is full of structural charm beauties. One of these appeals appearing in this speech is the parallelism Rhythm that came from the frequency of structural equivalents on the surface of the syntactic textures of the sermon text; which ultimately helps to formulate the general music of that text. This research intends to study parallelism Rhythm and its relation with religious meanings and content and its requirements to study its frequency in this sermon with a descriptive-analytical approach to illustrate the unique rhetoric of Nahj al-balagha. This article also tries to take a modest step towards understanding the beauty of the structure and content of this valuable book. The results of this study indicate that both types of parallelism Rhythm (singular parallelism and binary parallelism) are observed in this sermon, although the recurrence of binary parallelism is greater than the singular parallelism.